2013
DOI: 10.1111/ped.12092
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Questionnaire for children and adolescents: English norms and cut‐off points

Abstract: The normative and criterion-referenced PAQ values may be used to standardize and categorize PAQ scores in future youth population studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 47 publications
10
100
1
3
Order By: Relevance
“…Details to assess the PAQ-A score as cardiorespiratory fitness parameter have been published for English children. Our results are similar to obtained in the study of Voss et al (29), in which a cut-off points of 2.9 for boys and 2.7 for girls were established, using cardiorespiratory fitness as the criterion- Table III. PAQ-C score and steps/day cut-off points and sensitivity, specificity, likelihood ratios and predictive values, based on PA recommendations referenced standard.…”
Section: Discussionsupporting
confidence: 81%
“…Details to assess the PAQ-A score as cardiorespiratory fitness parameter have been published for English children. Our results are similar to obtained in the study of Voss et al (29), in which a cut-off points of 2.9 for boys and 2.7 for girls were established, using cardiorespiratory fitness as the criterion- Table III. PAQ-C score and steps/day cut-off points and sensitivity, specificity, likelihood ratios and predictive values, based on PA recommendations referenced standard.…”
Section: Discussionsupporting
confidence: 81%
“…Normative PAQ data for English youth reported cut off scores of all ages and therefore found an average mean of 3.007 (0.720) for boys and 2.695 (0.628) for girls [32]. The mean activity score for boys was 3.29 (SD=0.66), whereas the mean activity score for girls was 3.16 (SD=0.62) by a study reported by Welk et al [52].…”
Section: Physical Activity Questionnairesmentioning
confidence: 82%
“…As the PAQ are not designed to provide measures of time or intensity, classification relative to PA guidelines is impossible. Instead, various arbitrary PAQ-C score cut-off points have been proposed to categorize according to their selfreported PA [32]. Chen et al assigned PAQ scores ≤ 2 as "low activity, " >2 and ≤ 3 as "moderate activity, " and >3 as "high activity" [42].Therefore the total proportion PAQ-C scores are categorized as 26.3% children as low (≤ 2), 51.5%moderate (>2 and ≤ 3) and 22.1% high activity (>3).…”
Section: Physical Activity Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical activity questionnaires for adolescents or children (PAQ-A/C) were used to assess students RPA level (20). PAQ-A/C is a self-report instrument to assess last week RPA of adolescents and older children that includes 9 questions.…”
Section: Methodsmentioning
confidence: 99%